Evidence for sympatric speciation in a Wallacean ancient lake - Sutra, Nobu; Kusumi, Junko; Montenegro, Javier; Kobayashi, Hirozumi; Fujimoto, Shingo; Masengi, Kawilarang W. A.; Nagano, Atsushi J.; Toyoda, Atsushi; Matsunami, Masatoshi; Kimura, Ryosuke; Yamahira, Kazunori (Evolution, 2019)
Sympatric speciation has been demonstrated in few empirical case studies, despite intense searches, because of difficulties in testing the criteria for this mode of speciation. Here, we report a possible case of sympatric speciation in ricefishes of the genus Oryzias on Sulawesi, an island of Wallacea. Three species of Oryzias are known to be endemic to Lake Poso, an ancient tectonic lake in central Sulawesi. Phylogenetic analyses using RAD-seq-derived single nucleotide polymorphisms (SNPs) revealed that these species are monophyletic. We also found that the three species are morphologically distinguishable and clearly separated by population-structure analyses based on the SNPs, suggesting that they are reproductively isolated from each other. A mitochondrial DNA chronogram suggested that their speciation events occurred after formation of the tectonic lake, and existence of a historical allopatric phase was not supported by coalescent-based demographic inference. Demographic inference also suggested introgressive hybridization from an outgroup population. However, differential admixture among the sympatric species was not supported by any statistical tests. These results all concur with criteria necessary to demonstrate sympatric speciation. Ricefishes in this Wallacean lake provide a promising new model system for the study of sympatric speciation.